2021
DOI: 10.1002/2211-5463.13300
|View full text |Cite
|
Sign up to set email alerts
|

Reduced TREM2 activation in microglia of patients with Alzheimer's disease

Abstract: Loss‐of‐function variants of triggering receptor expressed on myeloid cells 2 (TREM2) increase the risk of developing Alzheimer's disease (AD). The mechanism through which TREM2 contributes to the disease (TREM2 activation vs inactivation) is largely unknown. Here, we analyzed changes in a gene set downstream of TREM2 to determine whether TREM2 signaling is modified by AD progression. We generated an anti‐human TREM2 agonistic antibody and defined TREM2 activation in terms of the downstream expression changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 99 publications
(151 reference statements)
0
23
0
Order By: Relevance
“…Triggering receptor expressed on myeloid cells 2 (Trem2) is a single pass transmembrane receptor that activates a range of signaling pathways associated with immune function through ligand binding ( 51 ). Trem2 has been used as a microglial activation marker and a general requirement for its activation ( 29 , 52 ). Galectin-3 can bind to the Trem2, activate microglia, and induce neuroinflammatory responses in an AD mouse model, our recent study confirmed that inhibition of endogenous Trem2 ligand ameliorates DCD by inhibiting oxidative stress and neuroinflammation ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Triggering receptor expressed on myeloid cells 2 (Trem2) is a single pass transmembrane receptor that activates a range of signaling pathways associated with immune function through ligand binding ( 51 ). Trem2 has been used as a microglial activation marker and a general requirement for its activation ( 29 , 52 ). Galectin-3 can bind to the Trem2, activate microglia, and induce neuroinflammatory responses in an AD mouse model, our recent study confirmed that inhibition of endogenous Trem2 ligand ameliorates DCD by inhibiting oxidative stress and neuroinflammation ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, APOE can act as a ligand for TREM2 and the TREM2-APOE pathway acts as a regulator that can help restore homeostatic microglia (Krasemann et al, 2017). Okuzono et al (2021) found that activation of TREM2 in AD may lead to anti-apoptotic signaling, immune responses and cytoskeletal alterations in microglia. On the contrary, CD33 inhibits anti-inflammatory signal transduction, cell adhesion and endocytosis of microglia, increasing the risk of AD (Ryan et al, 2017).…”
Section: Microglia-associated Immune Receptors and Alzheimer's Diseasementioning
confidence: 99%
“… 199 , 200 Moreover, it has been observed that TREM2 activation decreases with AD progression. 198 TREM2 activation was lower in AD microglia than in microglia from healthy subjects or patients with mild cognitive impairment. 198 TREM2 activation in AD may lead to anti-apoptotic signaling, immune response, and cytoskeletal changes in the microglia, supporting a protective role of TREM2 activation in AD.…”
Section: Potential Strategies To Combat Ad Based On Modifying the Act...mentioning
confidence: 81%
“… 198 TREM2 activation in AD may lead to anti-apoptotic signaling, immune response, and cytoskeletal changes in the microglia, supporting a protective role of TREM2 activation in AD. 198 Anti-TREM2-specific agonistic antibodies, such Hyb87, 4D9, 201 AL002 202 (the most advanced from Alector now in phase II clinical trial Supplemental Data 6 ) may become the most effective therapeutic agents against AD.…”
Section: Potential Strategies To Combat Ad Based On Modifying the Act...mentioning
confidence: 83%
See 1 more Smart Citation